2017
DOI: 10.3892/ol.2017.5897
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine triggers an alternative autophagy in DU145 cells

Abstract: Abstract. Tetrandrine (Tet), a potent lysosomal inhibitor, blocks autophagic flux and induces cancer cell death. Previously, the present authors identified the prostate cancer cell line DU145 to exhibit high sensitivity towards Tet in 11 cancer cell lines. In the present study, autophagy in Tet-treated DU145 cells was investigated. Similar to other cell lines, such as PC-3 and 786-O cells, Tet neutralized the acidity of lysosome and blocked autophagy in DU145 cells. However, Tet failed to induce microtubule-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…TET possesses a notable antitumor activity in numerous types of cancer, including gastric, lung, liver and colorectal cancer, both in vitro and in vivo ( 12 , 13 ). The mechanisms of action of TET are associated with multiple factors, such as modulating molecular signaling pathways ( 14 ), inducing cancer cell apoptosis ( 15 ), promoting cell cycle arrest ( 16 ) and increasing cell autophagy ( 17 ). Although TET has been approved in China for some types of cancer, such as acute myelogenous leukemia and advanced non-small cell lung cancer ( 18 , 19 ), it has not been yet approved in Japan as an antitumor drug for patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…TET possesses a notable antitumor activity in numerous types of cancer, including gastric, lung, liver and colorectal cancer, both in vitro and in vivo ( 12 , 13 ). The mechanisms of action of TET are associated with multiple factors, such as modulating molecular signaling pathways ( 14 ), inducing cancer cell apoptosis ( 15 ), promoting cell cycle arrest ( 16 ) and increasing cell autophagy ( 17 ). Although TET has been approved in China for some types of cancer, such as acute myelogenous leukemia and advanced non-small cell lung cancer ( 18 , 19 ), it has not been yet approved in Japan as an antitumor drug for patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine (Tet), a widely investigated compound, exhibits potent anti-tumor effects in lung cancer, prostate cancer, breast cancer and bladder cancer [1][2][3][4][5][6]. In bladder cancer, Tet induces apoptosis and reverses the epithelial-mesenchymal transition [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Atg5-independent autophagy has also been described in cells from fetal brains, livers, and hearts [47], as well as in human epidermis [51]. In addition to normal cells, alternative autophagy has also been reported in various cancer cell lines, including prostate DU145 cancer cells [54,55], erythroleukemia K562 cells [6], adenocarcinoma H1650 cells, and lung carcinoma A549 cells [56].…”
Section: Alternative Autophagy-a Short Overviewmentioning
confidence: 94%
“…It has been reported that no LC3 lipidation occurs during alternative autophagy [39]. Thus, the results based on LC3 conversion should be interpreted with caution [55]. Instead of LC3, Rab9, Syntaxin 7, and p-Ulk1 746 (p-ULK1 747 ) seem to be more appropriate potential markers [48,59].…”
Section: Detection Of Alternative Autophagymentioning
confidence: 96%